Korelasi Hemoglobin Dengan Indek Masa Tubuh dan Tekanan Darah Sebagai Skrining Pencegahan Stunting pada Remaja - Resmi Aini; Windadari Murni Hartini; Neini Nur’avia; Suci Lestariani (Jurnal Kesehatan, 2023)
There are 3 elements to the nutritional problems of Indonesian adolescents, namely malnutrition, overweight, and micronutrient deficiencies with anemia. Anemia has an impact on irregular heartbeats that affect blood pressure (systolic and diastolic). Deficiency and excess nutrition is a risk factor for anemia. Anemia in young girls can continue when they become mothers. During pregnancy, they are also more at risk of experiencing postpartum hemorrhage, giving birth to babies with low birth weight, babies born prematurely, or stillbirth. In addition, their children are more likely to be stunted. This type of research is Analytical Observational with a cross-sectional approach. The number of samples was 23 young women in the Darun Najah Orphanage, Depok, Sleman, Yogyakarta. Measuring blood pressure using a digital blood pressure device while Body Mass Index is calculated by measuring body weight and height. Hemoglobin levels in female adolescents were significantly related to BMI (Body Mass Index) and Diastolic blood pressure, but Hemoglobin levels were not significantly related to systolic blood pressure.